Comparison of different modified aluminosilicate networks for the removal of diclofenac. Issue 55 (25th November 2016) - Gamboa, P.A.; Ramírez-García, J.J.; Solache-Ríos, M.; Díaz-Nava, C.; Gallegos-Pérez, J.L.
Abstract: Different modified hexadecyltrimethylammonium (HDTMA) aluminosilicate networks were used to remove diclofenac (DS) from aqueous solutions, in order to know how important the networks of the aluminosilicates in adsorption processes are. HDTMA modified zeolitic tuff and HDTMA modified clay samples were characterized by X-ray Diffraction, Thermal Gravimetric Analysis, Fourier Transform Infrared Spectroscopy, and Scanning Electron Microscopy. The adsorption kinetics data were described by the pseudo-second-order kinetic model, and the Langmuir model described the isotherm of DS by the HDTMA modified zeolitic tuff (SMZ-25 and SMZ-50) which indicated chemical adsorption on homogeneous materials. The equilibrium isotherms for HDTMA modified clay (SMC-50) followed a linear behavior which is characteristic of sorption of organic solutes sorption by the partition mechanism. The maximum sorption capacities were 0.826 ± 0.004 mg/g for SMZ-25 and 0.880 ± 0.012 mg/g for SMC-50. According to the kinetic and isotherm results, SMZ-25 and SMC-50 showed the best properties to remove DS from aqueous solutions.